Target-independent high-throughput sequencing methods provide evidence that already known human viral pathogens play a main role in respiratory infections with unexplained etiology. Issue 1 (1st January 2019) - Pérez-Sautu, Unai; Wiley, Michael Ross; Iglesias-Caballero, María; Pozo, Francisco; Prieto, Karla; Chitty, Joseph Alex; García-García, María Luz; Calvo, Cristina; Casas, Inmaculada; Palacios, Gustavo
ABSTRACT: Despite the advanced PCR-based assays available, a fraction of the pediatric respiratory infections remain unexplained every epidemic season, and there is a perception that novel viruses might be present in these specimens. We systematically collected samples from a prospective cohort of pediatric patients with respiratory infections, that returned negative results by validated molecular RT–PCR assays, and studied them with a target-independent, high-throughput sequencing-based approach. We also included a matched cohort of children with no symptoms of respiratory infection, as a contrast study population. More than fifty percent of the specimens from the group of patients with unexplained respiratory infections were resolved. However, the higher rate of detection was not due to the presence of novel viruses, but to the identification of well-known viral respiratory pathogens. Our results show that already known viral pathogens are responsible for the majority of cases that remain unexplained after the epidemic season. High-throughput sequencing approaches that use pathogen-specific probes are easier to standardize because they ensure reproducible library enrichment and sequencing. In consequence, these techniques might be desirable from a regulatory standpoint for diagnostic laboratories seeking to benefit from the many advantages of these sequencing technologies.